El uso de las TIC´S en la enseñanza del inglés (Memorias Sifored - Encuentros Educación UAN, 2023)
English is a communicative competence and skill that continues to gain more relevance in the 21st century, which suggests that it is necessary to work from different areas to strengthen this second language. One aspect to take into account is the different teaching tools that are used to learn English and, often, although it is not expected, it is a factor that mediates between the teacher and the student, which allows producing methodological innovation and enhance the interest of students to learn. The objective of this study is to show the main factors or aspects related to the use of ICT in English language teaching. The methodology used in the present research was based on a systematic review of different articles and scientific journals, another aspect that was taken into account at the time of carrying out the selection of such, articles were their years of publication, which had to govern between 2018 and 2023, in this way we could ensure relevant results on how ICTs are used in the process of teaching a second language "English" and evidenced the positive and negative aspects to be considered as: the advantages of using technology in the classroom, how ICT motivated students to actively participate during the class and the complications that could arise from the recurrent use of ICT in the classroom.
Keywords: ICTs; english; innovation; teaching; learning